GAMBARAN KADAR SEROTONIN SERUM PADA PASIEN NYERI KRONIK YANG MENGALAMI INSOMNIA - Wiratmono Rahmadi,* Dani Rahmawati,* Endang Kustiowati,* Dwi Pudjonarko* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION CHRONIC PAIN IS A SERIOUS HEALTH PROBLEM WITH INSOMNIA AS ONE OF THE MAJOR COMORBIDITIES THERE IS A RECIPROCAL RELATIONSHIP BETWEEN CHRONIC PAIN AND INSOMNIA WITH THE ROLE OF SEROTONIN IN BETWEEN SEROTONIN IS A NEUROTRANSMITTER THAT MODULATES NEURAL ACTIVITY AND AFFECT VARIOUS NEUROPSYCHOLOGICAL PROCESSES INCLUDING PAIN AND SLEEP CYCLES